Anaerobic growth of Saccharomyces cerevisiae CEN.PK113-7D does not depend on synthesis or supplementation of unsaturated fatty acids. Issue 6 (19th August 2019) - Dekker, Wijb J C; Wiersma, Sanne J; Bouwknegt, Jonna; Mooiman, Christiaan; Pronk, Jack T
ABSTRACT: In Saccharomyces cerevisiae, acyl-coenzyme A desaturation by Ole1 requires molecular oxygen. Tween 80, a poly-ethoxylated sorbitan-oleate ester, is therefore routinely included in anaerobic growth media as a source of unsaturated fatty acids (UFAs). During optimization of protocols for anaerobic bioreactor cultivation of this yeast, we consistently observed growth of the laboratory strain S. cerevisiae CEN.PK113-7D in media that contained the anaerobic growth factor ergosterol, but lacked UFAs. To minimize oxygen contamination, additional experiments were performed in an anaerobic chamber. After anaerobic precultivation without ergosterol and Tween 80, strain CEN.PK113-7D and a congenic ole1Δ strain both grew during three consecutive batch-cultivation cycles on medium that contained ergosterol, but not Tween 80. During these three cycles, no UFAs were detected in biomass of cultures grown without Tween 80, while contents of C10 to C14 saturated fatty acids were higher than in biomass from Tween 80-supplemented cultures. In contrast to its UFA-independent anaerobic growth, aerobic growth of the ole1Δ strain strictly depended on Tween 80 supplementation. This study shows that the requirement of anaerobic cultures of S. cerevisiae for UFA supplementation is not absolute and provides a basis for further research on the effects of lipid composition on yeast viability and robustness. Abstract : Saccharomyces cerevisiae CEN.PK113-7D and a congenic ole1 null mutant grow anaerobically without supplementation of unsaturated fatty acids, which have long been considered as essential anaerobic growth factors for this yeast.